Kiprah Aktor Warganet melalui Media Sosial dalam Pemasaran Digital: Studi Kasus pada #HondaBeAT - Bambang Arianto; Andriya Risdwiyanto (Universitas Proklamasi 45, 2021)
This study aims to determine the role of netizen actors on social media in the digital marketing of a product brand, like #HondaBeAT. Nowadays, the use of social media to exchange information is increasing for the dissemination of messages and other contents. In the digital marketing ecosystem, social media plays an important role in introducing products, enhancing a positive image, and building relationships with customers. The use of social media platforms, such as Twitter and Instagram, has attracted the attention of the younger generation, especially the millennial generation (Y) and the post-millennial generation (Z). The level of effectiveness of digital marketing is also influenced and determined by the progress of netizen actors, such as followers, influencers, and buzzers. Their role is increasingly important to convey information more effectively through various product and service brand content on various social media platforms. This study uses a qualitative approach to analyze data from social media conversations on Twitter and Instagram within a certain period of time with the help of the Drone Emprit Academic (DEA) application. This research reveals the progress of netizen actors on the company’s official accounts of Twitter and Instagram as a basic understanding for designing and compiling digital marketing strategies using product brand hashtags. This study also found that the netizen actors studied had their respective roles in strengthening the delivery of messages and content on social media.